2010
DOI: 10.1007/s00414-010-0456-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of 10 X chromosomal STR loci in Indian population

Abstract: X chromosomal short tandem repeats have the potential to complement the analyses of the autosomal, Y chromosomal, and mitochondrial DNA markers in forensics and population genetics, and extensive research on X chromosomal markers is being carried out. In the present study, a decaplex for the co-amplification of ten X chromosomal microsatellite loci (DXS6807, DXS8378, DXS7132, DXS6809, DXS6789, DXS101, DXS7133, GATA172D05, HPRTB, and GATA31E08) was optimized and 749 blood samples of unrelated male individuals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, recent work focusing on X-chromosomal diversity in India (Mukerjee et al, 2010) reported no signs of LD for a set of 10 X-STR markers, seven of which were analyzed in this study. To address this issue, it would be essential to have data for all of the investigated loci in the populations that were involved in the process of gene flow.…”
Section: Ld Analysismentioning
confidence: 64%
See 4 more Smart Citations
“…However, recent work focusing on X-chromosomal diversity in India (Mukerjee et al, 2010) reported no signs of LD for a set of 10 X-STR markers, seven of which were analyzed in this study. To address this issue, it would be essential to have data for all of the investigated loci in the populations that were involved in the process of gene flow.…”
Section: Ld Analysismentioning
confidence: 64%
“…Unfortunately, the complete set of markers studied here was not available for Indian populations. However, recent work focusing on X-chromosomal diversity in India (Mukerjee et al, 2010) reported no signs of LD for a set of 10 X-STR markers, seven of which were analyzed in this study.…”
Section: Ld Analysismentioning
confidence: 64%
See 3 more Smart Citations